(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Relapse demonstrates a large problem in general health; the relapse effects on the family and the client together social contact with other people and financially. Objectives: To find out the relationship between the Psychological factors of relapse and sociodemographic data of psychotic patients attending teaching hospitals in AL_Furat Al-Awsat Governorates. Methodology: The design was (Descriptive-Correlational) used to describe the variables and the relationships that occur among them in this study. The sample was (a non-probability) purposive of (181) relapsed psychotic patients were selected from our patients centers from teaching hospitals in AL_Furat Al-Awsat Governorates, during the period from 9th May 2019 to 20th August 2019. The instrument included two parts: sociodemographic variables and the psychological factors associated with relapse. The researcher used descriptive statistics tools such as frequency, percentage, mean of score and used in inferential statistics such as Chi-Square. Results: The findings of the study indicate that (45.86%) of the sample their diagnosis was schizophrenia, (25.97%) were schizoaffective and (11.60%) were major depressive disorder with psychotic features. Also, the findings of the study indicate that (39.2%) of the study samples they have poor psychological factors, (34.8%) they have moderate psychological factors and (26%) they have good psychological factors. Conclusion: There is a high significant relationship between the most sociodemographic data and psychological factor (that included high express emotion and stigma factors).